Nucleic acid binding and intracellular localization of unr, a protein with five cold shock domains. - Jacquemin-Sablon, H (1994)
The unr gene was identified as a transcription unit located immediately upstream of N-ras in the genome of several mammalian species. While this genetic organization could be important for the transcriptional regulation of unr and N-ras, the function of the protein product of unr is unknown. unr is ubiquitously expressed and codes for an 85 kDa protein which is not closely related to previously characterized proteins. Nevertheless, a search for protein motifs has indicated the presence of five 'cold shock domains' within unr, a motif present in procaryotic cold shock proteins and in the vertebrate Y box factors. As these proteins have been reported to interact with nucleic acids, we investigated whether unr could bind to some classes of nucleic acids. We report here that unr has a high affinity for single-stranded DNA or RNA and a low affinity for double-stranded nucleic acids. Its low affinity for double-stranded DNA clearly distinguishes unr from the Y box factors. The binding of unr to RNA does not appear to depend upon extended sequence motifs but requires some level of sequence complexity as unr has only a low affinity for most simple polymers including polyA stretches. unr is also characterized by its low affinity for double-stranded and structured RNAs. We further determined that unr is mostly localized in the cytoplasm, and is in part associated with the endoplasmic reticulum. These studies indicate that unr is a novel single-stranded nucleic acid binding protein which is likely to be associated with cytoplasmic mRNA in vivo.